2013
DOI: 10.1590/s0034-8910.2013047004059
|View full text |Cite
|
Sign up to set email alerts
|

Survey of hearing disorders in an urban population in Rondonia, Northern Brazil

Abstract: RESULTS:The results showed that 3.8% (95%CI 2.17;5.45) of population were classifi ed in the disabling hearing impairment category. The prevalence of moderate hearing impairment was 3.4%; severe impairment was 0.4%; and profound hearing impairment was not found. CONCLUSIONS:The impairing hearing loss prevalence found in this study is within of the international prevalence for this level of hearing loss and smaller than observed in a previous study in the South region of Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 5 publications
(3 reference statements)
0
12
0
1
Order By: Relevance
“…However, this prevalence was lower than that described in a study conducted with 2,427 people in Rondônia to provide the first population-based data on deafness and hearing loss in Brazil. In this study, hearing loss was verified in 26.1% of the population (24) . In this context, it should be considered that only aging does not explain the high frequency of hearing loss in individuals with SS in the current study.…”
Section: Discussionmentioning
confidence: 55%
“…However, this prevalence was lower than that described in a study conducted with 2,427 people in Rondônia to provide the first population-based data on deafness and hearing loss in Brazil. In this study, hearing loss was verified in 26.1% of the population (24) . In this context, it should be considered that only aging does not explain the high frequency of hearing loss in individuals with SS in the current study.…”
Section: Discussionmentioning
confidence: 55%
“…In Brazil, there are few studies of the prevalence of hearing loss in the older population, and, when the studies are carried out, follow different collection methods (Bevilacqua et al, 2013;Cruz et al, 2009;Paiva et al, 2011). Paiva et al (2011) aimed at estimating the prevalence of hearing impairment among older adults in the city of São Paulo, but used a different question in their study, which encompassed issues related to difficulty in hearing and deafness in one ear and both ears, having created the variable "self-reported hearing loss" from the grouping of positive responses to these questions.…”
Section: Discussionmentioning
confidence: 99%
“…offering hearing loss as one of the options. Bevilacqua et al (2013) established the prevalence of hearing loss through a portable audiometer (frequencies of 1 kHz, 2 kHz, and 4 kHz) among 525 participants of all ages in the state of Rondônia, Brazil. In this same study, 11.4% of mild hearing loss was observed for the entire population, but when stratifying by age (≥ 60; n = 21), the authors found 39.5% of mild hearing loss, 28.9% moderate, and 2.6% severe in these participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tendo em vista o intuito de, posteriormente, submeter os manuscritos para apreciação de revistas científicas que seguem o estilo da American Psychological Association (APA), o mesmo foi adotado. na população de quatro a nove anos iguais a 1,3% (BEVILACQUA et al, 2013) a 12,1% (BÉRIA et al, 2007. No que se refere apenas às perdas incapacitantes (limiares auditivos de 31 dB ou mais para crianças abaixo de 15 anos) as prevalências encontradas nesta população foi de 2,86% (GONDIM et al, 2012) a 5,3% (BÉRIA et al, 2007.…”
Section: Considerações Iniciaisunclassified